Analisis Faktor Yang Berhubungan Dengan Usia Menopause di Puskesmas Wua-Wua Kota Kendari - La Rangki La Rangki; Heriviyatno J Siagian; La Ode Alifariki (Jurnal Kesehatan Komunitas, 2020)
Menopause period were decreased of estrogen hormone which causes women to experience complaints and can even interfere with activity. The purpose of this study is to determine analysis factors to menopause age in menopausal women at Wua-wua Public Health Center, Kendari City.This cross sectional study located in the Wua-Wua Health Center, Kendari City with population is all of the menopausal women who visited Puskesmas Wua-Wua Kendari City. 74 respondents are taken using a total sampling technique. Data collection using a questionnaire and analyzed using chi square statistical test at a value of Î± = 0.05.The results of this study indicate that the age of the respondents, normal category is 41.9%, fast category 17.6%, slow category 40.5%. The results of bivariate analysis using the Chi Square test showed a relationship between history of use of contraception with menopausal age (p 0.013 <Î± 0.05), BMI with menopausal age (p 0.005 <Î± 0.05), age and menopause (p 0,000 < Î± 0,05) and parity with menopausal age (p 0.000 <Î± 0.05).Contraception, Body Mass Index (BMI), age, parity related to age at menopause, while variables of employment status and educational status were not related to menopausal age. So that mothers, if they want to slow down the menopause, use hormonal contraception, regulate births or the number of children, and do physical activity so that they maintain ideal body weight.